2016
DOI: 10.1097/md.0000000000005153
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between 2 different doses of pregabalin and lidocaine on pain following propofol injection

Abstract: Background:Propofol, an intravenous anesthetic, often causes pain on injection, which can be very distressful to patients. We investigated the analgesic effect of pregabalin on pain following propofol injection, compared with lidocaine.Methods:In a randomized, double-blind, prospective trial, 120 patients were randomized into 3 groups of 40 each; who received oral placebo and intravenous lidocaine 40 mg with venous occlusion for 1 minute (group L, n = 40), oral pregabalin 75 mg and intravenous normal saline wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
3
0
5
Order By: Relevance
“…A study-blinded anesthesiologist measured score of injection pain of propofol using a 4-point scale (0 = none [negative response to questioning], 1 = mild pain [pain reported in response to questioning only, without any behavioral sign], 2 = moderate pain [pain reported in response to questioning and accompanied by a behavioral sign, or pain reported simultaneously without questioning], 3 = severe pain [strong vocal response or response accompanied by facial grimacing, arm withdrawal or tears]). [ 2 ] Thereafter, propofol-LCT1.5 mg/kg and rocuronium 0.8 mg/kg were administered for tracheal intubation, and anesthesia was maintained with desflurane 4% to 7% in 50% N 2 O/O 2 . Emergence reactions associated with pretreatment substances such as hypotension and bradycardia were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…A study-blinded anesthesiologist measured score of injection pain of propofol using a 4-point scale (0 = none [negative response to questioning], 1 = mild pain [pain reported in response to questioning only, without any behavioral sign], 2 = moderate pain [pain reported in response to questioning and accompanied by a behavioral sign, or pain reported simultaneously without questioning], 3 = severe pain [strong vocal response or response accompanied by facial grimacing, arm withdrawal or tears]). [ 2 ] Thereafter, propofol-LCT1.5 mg/kg and rocuronium 0.8 mg/kg were administered for tracheal intubation, and anesthesia was maintained with desflurane 4% to 7% in 50% N 2 O/O 2 . Emergence reactions associated with pretreatment substances such as hypotension and bradycardia were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Total seluruh kelompok penelitian dari seluruh studi adalah 51 kelompok. Terdapat 16 studi yang menggunakan lidokain, 1,3,4,5,6,8,10,13,14,16,17,18,19,20,22,24 11 studi yang menggunakan ketamin, 2,7,8,9,11,15,16,17,19,23,25 dan empat studi yang menggunakan fentanil. 7,9,11,12 Normal salin dan air suling dalam studi ini digunakan untuk metode pembutaan agar anestesiologis tidak dapat membedakan antar grup studi, dan terdapat tujuh studi yang menggunakan normal salin dan air suling.…”
Section: Penilaian Risiko Bias Pada Studi Individualunclassified
“…25 Ada 10 studi yang menggunakan oklusi vena sebelum diinduksi propofol, dan ada dua studi yang menggunakan tornikuet. 3,4,8,10,14,15,18,19,23,24 Luaran yang dicari oleh penulis adalah rata-rata dampak respons nyeri pada injeksi propofol dalam tiap penelitian. Ada 17 studi yang menggunakan metode Verbal Rating Scale (VRS), 2,4,5,6,8,10,11,12,14,15,16,20,21,22,23,24,25 terdapat empat studi yang menggunakan Visual Analog Scale (VAS) 7,9,18,19 dan empat studi menggunakan Numerical Rating Scale (NRS).…”
Section: Penilaian Risiko Bias Pada Studi Individualunclassified
“…Despite these positive aspects, patients can experience pain at injection of propofol and of these [6]. When used in the back of the hand, this value may increase to 60-80% of patients receiving propofol peripherically [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a signifi cant reduction in pain due to previous administration of intravenous opioid analgesics [10]. It has been shown that the use of pregabalin may also be useful in reducing pain at its injection, besides requiring less use of opioids for this purpose [7]. Another way to prevent this pain is with the administration of lidocaine, a local anesthetic drug, which can be administered immediately before or mixed with the injection of propofol, with doses up to 100mg in total [4].…”
Section: Introductionmentioning
confidence: 99%